Thyroid function and nutrient status in the athlete - Larson-Meyer, D. E.; Gostas, D. E. (Current Sports Medicine Reports, 2020)
Thyroid disease is common in the general population, especially in women, and also may be prevalent among athletes. Autoimmune disorders are the most common cause of thyroid disorders in countries with iodine-fortification programs; however, thyroid dysfunction can be brought on by nutritional factors, including insufficient energy intake and iodine, selenium, iron, and vitamin D deficiency. Additionally, strenuous exercise may be associated with transient alterations in thyroid hormones. While the development of thyroid related disorders has the potential to impact health and peak performance, typical clinical manifestations are highly variable, lack specificity, and are frequently confused with other health problems. The assessment process should focus on anthropometric changes, biochemical tests (thyroid panel), personal and family history, examination for appropriate signs and symptoms, and diet and environmental assessment that includes adequacy of energy, iodine, iron, selenium, and vitamin D intake/status along with excess stress and exposure to environmental contaminants and dietary goitrogens.